Exploring the meaning of life among Chinese adolescents with nephrotic syndrome: determinants and psychological correlates - Liang, Ying; Huang, Ruijie; Luo, Xiuzhuang; Mo, Shuyan; He, Zhichuan; Tian, Junhong; Yang, Lijuan; Xue, Yi; Luo, Xiaomi (Frontiers in Psychology, 2024)
Background: Adolescents with Nephrotic Syndrome (NS) confront unique challenges that influence their Meaning of Life (MOL), a concept crucial for psychological resilience. The chronic nature of NS and its associated burdens necessitate a deeper exploration of MOL and its determinants within this demographic, previously underexamined in research. This study aims to investigate MOL among Chinese adolescents with NS, identifying key factors influencing their sense of meaning and examining the interrelations with Subjective Well-Being (SWB) and Psychological Security (PS).Methods: Employing a cross-sectional survey design, we analyzed 150 adolescents with NS from Baise City, Guangxi, using the Purpose in Life (PIL) scale alongside PS and SWB scales. Sociodemographic and disease-related variables were assessed for their impact on MOL. Data analysis included descriptive statistics, multiple linear regression, and correlation analyses to explore predictors of MOL and its association with SWB and PS.Results: A significant proportion (62.0%) of participants exhibited MOL scores below the threshold, indicating diminished life meaning. Critical factors impacting MOL included 'left-behind' status, family structure, educational disruptions, and NS duration. Strong correlations emerged between MOL, SWB (r = 0.70, p < 0.01), and PS, highlighting the interdependence of these psychological dimensions. The study further revealed 'Proactivity' as a vital component of MOL, suggesting that despite their challenges, adolescents with NS maintain a keen engagement with life. Key aspects such as 'Certainty in Control', 'Mood of Melancholy or Pleasure', and 'Vitality' emerged as crucial for intervention.The findings underline the profound impact of NS on adolescents' MOL, influenced by both sociodemographic and disease-specific factors. By identifying key areas for psychological intervention, this study contributes to the holistic care and treatment of adolescents with NS, advocating for integrated approaches that address their unique challenges and support systems.